Assignment of the South Chinese Ordovician trilobite calymene paronai to Neseuretus - Turvey, S; Siveter, D (2007)
Calymene paronai Pellizzari, 1913 was described on the basis of an almost complete enrolled specimen from the Ordovician (probably the early Llanvirn Yangtzeella poloi Biozone) of southern Shaanxi, China. It represents one of the first Chinese trilobite species to have been established, but has been almost completely ignored by subsequent workers. This species is redescribed and reassigned to the Gondwanan inner shelf indicator calymenid Neseuretus, compared with other South Chinese taxa previously assigned to this genus, and interpreted as a senior synonym of N. concavus Lu, 1975.